Violência doméstica contra as mulheres: recepção de campanhas publicitárias de enfrentamento às violações de gênero a partir do olhar de vítimas e autores - Sousa, Jean Costa (2019)
This research has as context the investigation of how victims, authors and professionals - who work with those involved in this domestic violence - interpret the publicity campaigns to combat violence against women in Brasilia. And for this will be analyzed by women and men who are assisted in the Core Program for Family Care and the Domestic Violence Authors of the Federal District Government and professionals who perform psychosocial monitoring. Thus, understanding violence against women, gender-based violence, advertising campaigns with a social approach, reception study and pervading affirmative public policies is fundamental for the construction of the theoretical framework, which adds to the structure of the methodological path and the techniques used. to get to the results. It is pointed out that this phenomenon is a public health problem and, therefore, it is necessary to discuss public policies to combat violence against women, such as the Maria da Penha Law and support programs for them, in addition to those that work with women. authors. The creation of mechanisms in the media area, from citizenship with a gender perspective, is one of the pillars to break this scenario. We seek, therefore, to understand the process of domestic violence against women, as well as to understand how is the relationship between women and men, which may be relevant for understanding the reception transmitted in advertisements. However, to what extent it can contribute to triggering conflicting relationships between victims and perpetrators and exercising citizenship. In this aspect, we use as interpretative analysis methodology, from which we emphasize the categorization, description and interpretation as primordial procedures of the developed methodology. The results show that the publicity campaigns to combat domestic violence in Brasilia are lacking as to the way they are worked. Although the victims recognize themselves in the advertisements, they themselves claim that they did not live in that kind of situation. And the authors deny the violence. They do not feel represented in advertising because they do not consider themselves aggressive. NAFAVD employees point out that it is necessary to work in the advertising campaigns new perspectives: gender, machismo, all kinds of violence that Law 11.340 / 2006 exposes, ethnic-racial issue, the consequences and penalties that the author may suffer if he commits act of domestic violence, the women host services and where to look for them. In addition, we realize that there is no investment in affirmative public policies in the media to combat domestic violence against women in Brasilia.